Enhancing literacy competence of 5th-grade students at SDN 3 Kerticala through learning assistance - Darojatun Nura (Universitas Pendidikan Indonesia, 2023)
The Ministry of Education and Culture of the Republic of Indonesia has implemented Kurikulum Merdeka policy to improve the quality of education. This policy contains assessment points covering literacy and numeracy. One of the instruments used in this policy is Asesmen Kompetensi Minimum (AKM), a tool for teachers to analyze student learning outcomes. To help teachers improve student literacy, a team of Kampus Mengajar Program batch 5 at SDN 3 Kerticala carried out community service that focused on helping the learning process of class V students at SDN 3 Kerticala. In this community service, 12 students of SDN 3 Kerticala took part in a learning assistance program run by a team of students from the Kampus Mengajar program. Implementing community service activities is filled with activities that can increase student literacy and play an essential role in assisting teachers in measuring and assessing student achievement at AKM. Data from the trial results after the implementation of learning assistance shows that the percentage of students who achieve competency has increased compared to the results obtained before the assistance. During the implementation of the assistance program, it was found that students needed to achieve specific competencies optimally. These findings can encourage teachers to optimize teaching and learning strategies that align with students' needs and learning styles. Abstrak Kementerian Pendidikan dan Kebudayaan Republik Indonesia telah menerapkan kebijakan Kurikulum Merdeka untuk meningkatkan kualitas pendidikan. Kebijakan ini berisi pokok penilaian yang meliputi literasi dan numerasi. Salah satu instrumen yang digunakan dalam kebijakan ini adalah Asesmen Kompetensi Minimum (AKM), yang berperan sebagai alat bagi guru untuk menganalisis hasil belajar siswa. Untuk membantu guru mengupayakan peningkatan literasi siswa, tim mahasiswa Program Kampus Mengajar Angkatan 5 yang bertugas di SDN 3 Kerticala melaksanakan pengabdian kepada masyarakat yang difokuskan pada pendampingan proses pembelajaran peserta didik kelas V di SDN 3 Kerticala. Pada pengabdian ini, terdapat 12 peserta didik dari SDN 3 Kerticala yang mengikuti program pendampingan belajar yang dijalankan oleh tim mahasiswa program Kampus Mengajar. Pelaksanaan kegiatan pengabidan diisi dengan aktivitas yang dapat meningkatkan literasi peserta didik dan berperan penting dalam membantu guru dalam mengukur dan menilai pencapaian peserta didik pada AKM. Hasil dari data uji coba setelah pelaksanaan pendampingan pembelajaran menunjukkan bahwa persentase siswa yang mencapai kompetensi mengalami peningkatan dibandingkan dengan hasil yang diperoleh sebelum melaksanakan pendampingan. Selama pelaksanaan program pendampingan, ditemukan bahwa beberapa kompetensi tertentu tidak dicapai oleh peserta didik secara maksimal. Temuan ini dapat dijadikan perhatian bagi para guru untuk mengoptimalkan strategi belajar mengajar yang lebih sesuai dengan kebutuhan dan gaya belajar siswa. Kata Kunci: AKM; kompetensi literasi; kompetensi numerasi; pendampingan belajar.